Effects of high-intensity interval training on physical performance, systolic blood pressure, oxidative stress and inflammatory markers in skeletal muscle of spontaneously hypertensive rats - D’Almeida, Thaynara Zanoni; Gomes, Mariana Janini; Engel, Leticia Estevam; Giometti, Ines Cristina; Ferreira, Natalia Zamberlan; Stuani, Rafael; Corrêa, Camila Renata [UNESP]; Castoldi, Robson Chacon [UNESP]; Nunes, Sarah Gomes; Aguiar, Andreo Fernando; Castilho, Anthony César; Okoshi, Marina Politi [UNESP]; et al. (Public Library of Science (PLoS), 2025)
Aim To investigate whether high-intensity interval training (HIIT) improves physical performance, systolic blood pressure, and markers of oxidative stress and inflammation in skeletal muscle of spontaneously hypertensive rats (SHR). Methods Nineteen male SHR rats were randomly assigned to two groups: sedentary (SHRC) and trained (SHR+T). The SHR+T group trained five times a week for eight weeks on a treadmill, while the SHR group remained without any exercise stimulus throughout the experimental period. Maximum physical performance and systolic blood pressure (SBP) were assessed before and after the training period. The following variables were measured in the tibialis anterior (TA) muscle: gene expression of the NADPH oxidase complex (NOX2, NOX4, p22phox, p47phox) and the NF-kB pathway (NF-kB and Ik-B), lipid peroxidation (malonaldehyde; MDA), protein carbonylation, hydrophilic antioxidant capacity (HAC) and pro-inflammatory cytokines (IL-6 and TNF-α). Results SHR+T rats showed higher physical performance and levels of IL-6, and lower SBP and protein carbonylation (p<0.05), compared with SHRC rats. No significant differences (p>0.05) were observed in the other variables. Significance Our results indicate that HIIT is an effective non-pharmacologic strategy to improve physical performance, reduce SBP, and modulate the skeletal muscle oxidative damage and inflammation in hypertensive rats.